(untitled) (Medico Legal Update, 2020)
Performance is the result of quality and quantity of work achieved by employees in carrying out their duties in accordance with the responsibilities given to them. The role of reliable and professional employees is very helpful in improving organizational performance. The quality of employees who are still far from adequate will certainly affect the achievements. This study aims to analyze the Influence of Job Embeddednes and Work Engagement on Improving Employee Performance in RSUD Haji of South Sulawesi Province in 2020. The type of research conducted is quantitative research using observational studies with cross sectional study design. The sample in this study were employees who worked at RSUD Haji with 240 respondents. The results showed there was an influence of job embeddedness on employee performance (p = 0,000), there was an influence of job embeddedness on work engagement (p = 0,000), there was an influence of work engagement on performance (p = 0,000), and there was no influence of job embeddedness on employee performance through work engagement (coefficient = 0.146). It is recommended to the hospital management to increase the embeddedness and engagement of employees, where employees can feel the compatibility of the work and improve the formal or informal relationship between an employee and the hospital environment so that the impact on improving the quality and performance of the hospital.